Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s42003-020-1091-1
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic insights of body plan transitions from bilateral to pentameral symmetry in Echinoderms

Abstract: Echinoderms are an exceptional group of bilaterians that develop pentameral adult symmetry from a bilaterally symmetric larva. However, the genetic basis in evolution and development of this unique transformation remains to be clarified. Here we report newly sequenced genomes, developmental transcriptomes, and proteomes of diverse echinoderms including the green sea urchin (L. variegatus), a sea cucumber (A. japonicus), and with particular emphasis on a sister group of the earliest-diverged echinoderms, the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 65 publications
5
53
0
Order By: Relevance
“…A large proportion of Eumetazoa shows a bilaterally symmetric body plan. Though adult echinoderms develop pentameral symmetry, they are bilaterally symmetric at least at their larval stage [1]. Exceptions, especially with regard to the head and face, are rare.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of Eumetazoa shows a bilaterally symmetric body plan. Though adult echinoderms develop pentameral symmetry, they are bilaterally symmetric at least at their larval stage [1]. Exceptions, especially with regard to the head and face, are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al . (2018) proposed that Hox6 was lost before the split of Echinozoa and Asterozoa (Li et al, 2018), while Li et al . (2020) suggested that the loss of Hox4 or Hox6 was a lineage-specific event (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2018) proposed that Hox6 was lost before the split of Echinozoa and Asterozoa (Li et al, 2018), while Li et al . (2020) suggested that the loss of Hox4 or Hox6 was a lineage-specific event (Li et al, 2020). We found that Hox4 and Hox 6 were missing in the genomes of both C. heheva and A. japonicus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to echinoderms, considerable evidence supports the view that alx1 arose very early in echinoderm evolution through gene duplication, relatively quickly acquired a robust, biomineralization-related function, and was subsequently co-opted into the early embryo in echinoderm taxa that possess larval skeletons (echinoids and ophiuroids; Khor and Ettensohn, 2017;Shashikant et al, 2018). The biomineralizing cells of the ancestral echinoderm, which were likely of mesodermal origins, expressed alx1, ets1, erg, vegfr, and other components of a core skeletogenic program, as well as an assortment of more rapidly evolving biomineralization effector proteins (Gao and Davidson, 2008;Dylus et al, 2018;Erkenbrack and Thompson, 2019;Li et al, 2020). To draw inferences concerning the evolution of alx gene expression and function more deeply within Ambulacraria (echinoderms and hemichordates), it will be important to learn more about the single alx gene of hemichordates, including its pattern of expression, gene targets, and role in the formation of the small, calcareous skeletal elements of adult hemichordates (Cameron and Bishop, 2012) and to more precisely determine the embryological origins of the alx1-expressing cells of adult echinoderms, which are more relevant to the ancestral echinoderm condition than the more commonly studied larval forms.…”
Section: Alx Genes and The Evolution Of Deuterostome Biomineralizationmentioning
confidence: 99%